Pembentukan Karakter Percaya Diri Melalui Kegiatan Muhadharoh di SMP 2 Negeri Bukitinggi - Adilah, Salma (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to explore the role of muhadarah as an effective method in forming character and increasing students' courage in coming forward. The main focus of this research is at SMPN 2 Bukittinggi, where muhadarah has been implemented as part of the curriculum to shape student character. The research method uses a qualitative approach by collecting data through observation, interviews with teachers and students, as well as content analysis from class notes. The results show that muhadarah, a religion-based discussion or presentation, plays an important role in shaping students' character, especially in increasing their courage to speak in public. In its implementation, muhadarah provides students with the opportunity to express their thoughts, hone their speaking skills, and build self-confidence. By discussing topics relevant to everyday life and moral values, students learn to openly confront diverse views and sharpen their arguments. These findings show that muhadarah is not only a religious activity, but also an effective means of forming student character. By facilitating positive interactions and building public speaking skills, muhadarah helps students develop the courage necessary to perform confidently in a variety of situations. In conclusion, muhadarah at SMPN 2 Bukittinggi has proven itself to be an effective tool in shaping students' character and increasing their courage. The recommendation from this research is to further integrate similar activities into the school curriculum as an integral part of student character formation